Non-Resident Land Ownership and Land Value in Two Eastern Townships of Quebec : A preliminary investigation - Rose, Curtis (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1975)
The papers probes the indirect relationship between land value and various types of landowners: resident landowners, and 'local', 'provincial', 'national' and 'foreign' non-resident landowners. Data on the number of landowners, the acreage held and the assessed value of buildings and land in two rural Québec municipalities are examined using plotted "surfaces" of land value and several non-parametric statistical approaches. The levels of non-resident ownership are found to be relatively high with 'local' and 'provincial' non-residents holding the bulk of the non-resident acreage. A significant association is found to exist between the total assessed value of land and buildings and the type of landowner in both municipalities.